Komunikasi Pemerintah Melalui Media Center Gugus Tugas Percepatan Penanganan Covid-19 Kepada Publik - Rika Oktariani; AG Eka Wenats Wuryanta (President University, 2020)
Abstract Corona Virus Disease 19 or Covid-19 is a worldwide pandemic. A surprising new generation of influenza virus. Instantly shocked the whole world. Indonesia is no exception. Since the first Covid-19 case emerged, relevant authorities such as the ministry of health, disaster management agencies, as well as public health services such as hospitals have experienced